Characteristics of Optic Neuritis in South Korean Children and Adolescents: A Retrospective Multicenter Study - Kyung-Ah Park; Hee Kyung Yang; Jinu Han; Seong-Joon Kim; Sung Eun Park; Haeng-Jin Lee; Sueng-Han Han; Sei Yeul Oh; Jeong-Min Hwang (Journal of Ophthalmology)
Purpose. To analyze the clinical characteristics and prognosis of optic neuritis (ON) in pediatric patients aged <19 years in South Korea. Methods. This multicenter retrospective cohort study included 127 pediatric patients (median age: 10.3 (IQR: 7.3–14.2) years; female, 62.2%) who experienced ON for the first time between January 2004 and January 2018, with data obtained from five tertiary university-based hospitals in Korea. When ON was bilateral, the worse eye was selected for analysis. The baseline clinical characteristics and prognoses of patients, as well as the associations between these parameters, were analyzed. Results. The baseline clinical characteristics of the patients were as follows: best-corrected visual acuity (BCVA) < 20/200, 65.9%; pain on eye movement, 47.2%; optic disc swelling, 66.9%; and bilateral involvement, 41.7%. Among 101 patients who were followed up for ≥6 months, 48 (47.5%), 12 (11.9%), 19 (18.8%), 13 (12.9%), and 9 (8.9%) had been diagnosed with isolated ON, recurrent ON, multiple sclerosis (MS), neuromyelitis optica spectrum disorder (NMOSD), and acute disseminated encephalomyelitis (ADEM)-related ON, respectively. At the latest visit, 81.9% and 71.1% had achieved BCVA of ≥20/40 and ≥ 20/25, respectively. Only disc swelling at presentation was associated with poor baseline BCVA (coefficient: 0.31, P=0.004) and greater improvement in BCVA (coefficient: 0.49, P = 0.001P=0.001); there were no significant associations between the baseline factors and final BCVA. Conclusions. This study demonstrated pediatric ON-related clinical characteristics and visual outcomes in South Korea. Within this cohort, in about 40.6% of patients, ON was associated with other demyelinating diseases, namely, MS, NMOSD, and ADEM.